2007
DOI: 10.1210/en.2007-0195
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-Induced Expression of Tumor Necrosis Factor α-Converting Enzyme/A Disintegrin and Metalloprotease-17 Impacts Porcine Cumulus Cell Oocyte Complex Expansion and Meiotic Maturation via Ligand Activation of the Epidermal Growth Factor Receptor

Abstract: The epidermal growth factor (EGF)-like growth factors, amphiregulin (AREG) and epiregulin (EREG), are expressed in murine cumulus oocyte complexes (COCs) where they impact the function of cumulus cells and oocyte maturation during LH-mediated ovulation. Because TNFalpha-converting enzyme (TACE)/a disintegrin and metalloprotease-17 (ADAM17) is essential for ectodomain shedding of AREG and EREG from the surface of other cell types, the expression and function of TACE/ADAM17 was analyzed in a porcine COC culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 39 publications
6
70
0
Order By: Relevance
“…Using this in vitro system, Ang II significantly amplified the positive effect of LH on PTGS2 (mRNA and protein expression), AREG, EREG, and plasminogen activators (Portela et al 2011). A dramatic upregulation of ADAM17, an essential factor for the initial ovulatory process (Yamashita et al 2007), was also observed 1 h post-treatment with Ang II. This early effect of Ang II preceded the induction of LH-induced genes, such as AREG, EREG, and PTGS2 by 2-5 h. Galardin, a broad-spectrum matrix metalloproteinase inhibitor, completely blocked the effects of LHC Ang II, demonstrating that sheddase activity is the direct target of Ang II.…”
Section: Ang II Signaling and Receptors Near Ovulationmentioning
confidence: 80%
“…Using this in vitro system, Ang II significantly amplified the positive effect of LH on PTGS2 (mRNA and protein expression), AREG, EREG, and plasminogen activators (Portela et al 2011). A dramatic upregulation of ADAM17, an essential factor for the initial ovulatory process (Yamashita et al 2007), was also observed 1 h post-treatment with Ang II. This early effect of Ang II preceded the induction of LH-induced genes, such as AREG, EREG, and PTGS2 by 2-5 h. Galardin, a broad-spectrum matrix metalloproteinase inhibitor, completely blocked the effects of LHC Ang II, demonstrating that sheddase activity is the direct target of Ang II.…”
Section: Ang II Signaling and Receptors Near Ovulationmentioning
confidence: 80%
“…Transcription of EGF-p is induced by cAMP activation of PKA, leading to the activation of the cAMP-response element (CRE) site in the gene's promoter region via a p38MAPK-CREB-dependent process (Richards 2001, Shimada et al 2006, Fan et al 2009). Mature form EGF-p are cleaved from mural granulosa cells and bind to the EGF receptor (ERBB1), expressed on mural granulosa cells (autocrine) as well as on CCs (paracrine) (Hsieh et al 2007, Yamashita et al 2007. Ligand binding in both cell types leads to receptor dimerisation and auto-phosphorylation on multiple tyrosine residues, which induce downstream RAS and, ultimately, ERK1/2 activation (Yamashita et al 2007, Fan & Richards 2010).…”
Section: Lh Surge and Camp Spike Activate The Egf Networkmentioning
confidence: 99%
“…Mature form EGF-p are cleaved from mural granulosa cells and bind to the EGF receptor (ERBB1), expressed on mural granulosa cells (autocrine) as well as on CCs (paracrine) (Hsieh et al 2007, Yamashita et al 2007. Ligand binding in both cell types leads to receptor dimerisation and auto-phosphorylation on multiple tyrosine residues, which induce downstream RAS and, ultimately, ERK1/2 activation (Yamashita et al 2007, Fan & Richards 2010). ERK1/2 consequently promotes the production of prostaglandin E2 by upregulating prostaglandin synthase 2 expression.…”
Section: Lh Surge and Camp Spike Activate The Egf Networkmentioning
confidence: 99%
“…For example, urokinase plasminogen activator, tissue plasminogen activator, ADAM17, ADAMTS1, and ADAMTS4 have been shown to be synthesized and secreted by cumulus cells (D'Alessandris et al 2001, Shimada et al 2004, Yamashita et al 2007). The proteolytic activity of ADAMTS1 has been associated with expansion of the cumulus matrix and remodeling of the follicle wall before ovulation (Russell et al 2003, Shimada et al 2004, Brown et al 2010, but has also a critical function in the timely degradation of the cumulus matrix after ovulation.…”
Section: Discussionmentioning
confidence: 99%